Children of Facundo : caudillo and gaucho insurgency during the Argentine state-formation process (La Rioja, 1853-1870) - De la Fuente, Ariel (E-Duke books scholarly collection., 2000)
Combines peasant studies and cultural history to revise the received wisdom on nineteenth-century Argentinian politics and aspects of the Argentinian state-formation process.